Equality in the Home and in the Community: a Multilevel Longitudinal Analysis of Intimate Partner Violence on the Ecuadorian-Colombian Border - Treves-Kagan, Sarah (Journal of family violence, 2022)
Intimate partner violence (IPV) effects over a third of Latin American women and results in significant health, economic and social consequences. While theory suggests that increasing the status of women, in their homes and neighborhoods, should prevent IPV, little empirical work has tested this in South America, in particular examining neighborhood-level indicators. We conduct multilevel analysis to identify predictors of recent emotional and physical and/or sexual IPV within a longitudinal sample of 1312 low-income women living in northern Ecuador, near the Colombian border. Status indicators, measured at the household and neighborhood-level, included women’s asset ownership, intra-household decision making, labor force participation, and education, age, and salary relative to male partner. Females’ increasing participation in household decision-making (between time 1 and time 2) was associated with decreased risk of physical and/or sexual (AOR: 0.41, 95% CI: 0.21, 0.78) and emotional IPV (AOR: 0.57, 95% CI: 0.30, 1.06), although the latter was marginally significant. Increases in neighborhood-level decision-making was protective against emotional IPV (AOR: 0.78, 95% CI: 0.61, 0.99). Women with lower education than their partners were significantly more likely to experience IPV than women with the same or more education as their partner. Indicators of economic status of women were not associated with IPV outcomes in the expected directions. Findings support policies and interventions seeking to raise the status of women as a mechanism to reduce IPV. Future research can explore economic empowerment and IPV, as well as the interaction between household and neighborhood-level factors.